Internalized weight stigma and intuitive eating among stressed adults during a mindful yoga intervention: associations with changes in mindfulness and self-compassion - Tosca D. Braun (Taylor & Francis Group, 2021)
Purpose Internalized weight stigma (IWS) is common in the United States of America across body weight categories, and is implicated in the development of distress and unhealthy eating behaviors (e.g. overeating, disordered eating) that can foster poor cardiometabolic health. While emerging intervention research shows early promise in reducing IWS, long-term efficacy is unclear and novel strategies remain needed. This analysis examined whether participation in a mindful yoga intervention was associated with reduced IWS and increased intuitive eating, an adaptive eating behavior, and whether these changes correlated with each other or with changes in mindfulness and self-compassion. Methods Participants were stressed adults with low fruit and vegetable intake (N = 78, 64.1% White, M. Body Mass Index  25.59 ± 4.45) enrolled in a parent clinical trial of a 12-week mindful yoga intervention. Validated self-report measures of IWS, intuitive eating, mindfulness, and self-compassion were administered at pre-treatment, mid-treatment (8 weeks), post-treatment (12 weeks), and 4-month follow-up (24 weeks). Results Linear mixed modeling revealed significant improvements in IWS and intuitive eating across the four timepoints (p < .001). Reduced IWS correlated with increased intuitive eating pre- to post-treatment (p = .01). Improved self-compassion and mindfulness correlated with intuitive eating (both p = . 04), but not IWS (p = .74 and p = .56, respectively). Conclusion This study offers preliminary support for the hypothesis that mindful yoga may promote intuitive eating and reduce IWS among stressed adults with poor diet, and suggests that changes in these factors may co-occur over time. Further investigation with controlled designs is necessary to better understand the temporality and causality of these relationships. Trial registration: ClinicalTrials.gov identifier: NCT02098018.